ANTIOXIDANT POTENTIAL OF ARABICA COFFEE PROCESSED BY HONEY METHOD - Arum, Ayu Puspita; Patricia, Susan Barbara; Savitri, Dyah Ayu; Setiyono, Setiyono (Jurnal Agroindustri, 2025)
This study investigated the impact of different coffee processing methods, the natural method, and fermentation with yellow, red, and black honey methods on the bioactive compounds of Arabica coffee using a Randomized Complete Block Design in five replicate experiments. The antioxidant activity, phenolic, flavonoid, caffeine, total soluble solid content, and pH value were determined. The results showed that the honey processing method could improve bioactive compounds more than the natural method, with higher levels of antioxidants, phenolic, flavonoid, and total soluble solid contents but lower caffeine content and pH value. Arabica coffee-treated yellow honey exhibited the highest Increase in antioxidant activity. These findings suggest that coffee-treated yellow honey could be a functional food.